Pengembangan Media Pembelajaran Permainan Ludo Kimia Berbasis Chemo-Edutainment (CET) Pada Materi Termokimia Kelas XI - Zeny Afriska Barutu; Lisnawaty Simatupang (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The study aims to determine the feasibility of chemo-edutainment (CET)-based chemical ludo media on thermochemical material for grade XI students. This research uses a modified ADDIE development model where only the analysis, design and development stages are carried out. This research was conducted at SMA Negeri 11 Medan which was held for 5 months. The validity of chemical ludo media is obtained from the validation results of lecturers and teachers and the respondents' assessment of this media is obtained from the results of teacher and student responses. The validation data obtained from material experts and media experts on chemical ludo respectively obtained a percentage of 87.30% and 85.75% which is included in the very high or valid category. The results of respondents' assessment of chemical ludo media by 3 teachers with an average percentage of 86.94% and 35 students obtained an average percentage of 86.00% which is included in the very high category. Based on the results of expert validation and respondent assessment, it can be concluded that this chemical ludo media is suitable for use in thermochemical learning.